Analysis of the Short-Term and Long-Term Impacts of the Coronavirus Crisis on International Climate Policy - Manuel Andreas Knoll; Zehra Aşkınsena İlkılıç (Alternatif Politika)
The coronavirus pandemic has caused far-reaching precautionary measures around the world. Governments’ attempts to get the coronavirus under control have led to the negligence of other important policy areas. Climate policy in particular has been significantly influenced and lost importance on the political agendas of states after the outbreak. Over time, the coronavirus will either disappear or lose its initial impact due to medical measures. Two years after the outbreak of the coronavirus, this paper aims to analyse and evaluate the short-term and long-term impacts of the coronavirus crisis on international climate policy. It is important to analyse how it has shaped international climate policy and what lessons can be learned for dealing with climate change. The analysis is based on the principles and regular functioning of the International Climate Change Regime.